Construction and Clinical Translation of Causal Pan-Cancer Gene Score Across Cancer Types - Tao, Shiyue; Ye, Xiangyu; Pan, Lulu; Fu, Minghan; Huang, Peng; Peng, Zhihang; Yang, Sheng (Frontiers in Genetics, 2021)
Pan-cancer strategy, integrative analysis for different cancer types, might explain oncogenesis and identify the biomarkers with larger statistical power and robustness. Fine-mapping defines the casual loci and fills in the gap where genome-wide association studies (GWAS) only identify thousands of cancer-related loci. Here, we develop a new strategy for defining causal loci using pan-cancer and fine-mapping assumption, constructing CAusal Pan-cancER gene (CAPER) score and validating its performance using internal and external validation with 1,287 individuals and 985 cell lines. Using summary statistics of 15 cancer types, we defined 54 causal loci in 15 potential genes. Using the Cancer Genome Atlas (TCGA) training set, we constructed CAPER score and divided the cancer patients into two groups. Using three validation sets, we found that 19 cancer-related variables were statistically significant between two CAPER score groups and that 81 drugs had significantly different drug sensitivity between two CAPER score groups. We hope our strategies for selecting causal genes and for constructing CAPER score provide valuable clues for guiding management from the perspective of different cancers.